2011
DOI: 10.1109/tvlsi.2009.2033699
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Power Gating During Mode Transition

Abstract: Abstract-With the technology moving into the deep sub-100-nm region, the increase of leakage power consumption necessitates more aggressive power reduction techniques. Power gating is a promising technique. Our research emphasizes that with the latest and future technologies, power gating operates frequently in its transition mode, especially for aggressive leakage reduction. The dynamic characteristics of power gating during its mode transition is critical for making design decision. Hence we derive a fast, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In power gating scheme, the leakage currents are almost minimized by introducing the external header and footer transistors. These transistors eliminate the path exiting between V DD to ground when the devices are in quiescent mode [77] [78].…”
Section: Power Gating Techniquesmentioning
confidence: 99%
“…In power gating scheme, the leakage currents are almost minimized by introducing the external header and footer transistors. These transistors eliminate the path exiting between V DD to ground when the devices are in quiescent mode [77] [78].…”
Section: Power Gating Techniquesmentioning
confidence: 99%
“…In [5] and [11], a need for wakeup latency estimation arises to quantify the effectiveness of proposed ground-bounce reducing techniques and intermediate strength power gating techniques respectively under a wakeup time constraint. In [14], Xu et al have proposed numerical approaches for estimation of as a function of time in sleep mode. To extend the same method to wakeup mode, it is necessary to incorporate size dependent sleep transistor current characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…In [14], compact models for leakage current have been derived at gate and circuit levels in a hierarchical way. It was shown that the leakage current can be represented by a voltage controlled current source (VCCS) as in Fig.…”
Section: Power-gated Logic Cluster Modelmentioning
confidence: 99%
“…An automated gate biasing technique has been developed to determine the gate bias voltage which minimizes leakage current [8]. Power gating characterization at early stages of the design process has been proposed [9]. Novel power gating approaches that utilize nano-electro-mechanical power switches with zero leakage current (off state) rather than MOS power switches have been examined [10].…”
Section: Introductionmentioning
confidence: 99%